2013
DOI: 10.1111/odi.12210
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between tongue brushing and halitosis in children: a randomized controlled trial

Abstract: Tongue brushing did not provide an additional benefit to the treatment for malodour. According to the microbiological culture results, a specific bacterium responsible for halitosis in children could not be identified and more sensitive methods might be used for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…The most common groups of oral bacteria in children with IOH are Veillonella spp., Prevotella spp., Fusobacterium spp. However, there is no difference in the abundance of these microorganisms in children with IOH and those without [110].…”
Section: Chemical Compound Bacteriamentioning
confidence: 84%
See 1 more Smart Citation
“…The most common groups of oral bacteria in children with IOH are Veillonella spp., Prevotella spp., Fusobacterium spp. However, there is no difference in the abundance of these microorganisms in children with IOH and those without [110].…”
Section: Chemical Compound Bacteriamentioning
confidence: 84%
“…In turn, the presence of bacteria, such as Firmicutes, Proteobacteria, Bacteroidetes, Actinobacteria, and Fusobacteria, was demonstrated in both the samples from examined and control groups. Firmicutes was the most abundant phylum in saliva samples from both groups [110,111].…”
Section: Chemical Compound Bacteriamentioning
confidence: 96%
“…By decreasing the nutrient supplies to the bacteria, bacteria counts on the tongue and total VSCs in the oral cavity are reduced [ 16 - 18 ]. Many studies of various mouth rinse applications and tongue cleaning procedures have been conducted [ 19 - 21 ]. However, few studies have compared the effect of simultaneous chemical and mechanical procedures on the reduction of VSCs in subjects with oral malodor.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed wider and thicker tongue coating increased the risk of oral malodor. 3,13,18,[22][23][24] Therefore, the absence of tongue cleaning would deteriorate oral malodor in dental patients. The use of mouthwash is proved to be one of the measures to decrease the clinical oral malodor.…”
Section: Discussionmentioning
confidence: 99%